POLEMIK MENINGKATNYA PERKAWINAN ANAK: REALITAS DAN PENCEGAHANNYA - Tantimin, Tantimin (Maleo Law Journal, 2022)
The Marriage Law stipulates that the minimum age for marriage is 19 (nineteen) years old for men and woman. However, there are still many people who practice marriage to children under the age of 19 (nineteen). The practice of child marriage can due to various factors, and has many negative impacts on children. The Covid-19 pandemic is one of the reasons for the increase in the number of child marriage in Indonesia. This study uses a normative juridical legal research method, based on written regulations and a literature study that examines aspects, theories, structures, and legal explanations related to this research. The data used is secondary data obtained from literature study. The approach used in this research is statutory approach. There is a Child Protection Law which is the legal umbrella in eradicating child marriage in Indonesia, but on the other hand, there are still many challenges in reducing the number of child marriage practices, one of which is the regulation related to marriage dispensation and the incessant criminal acts carried out under the guise of child marriage.